Development of Electrical Laboratory Information System using Model View Controller Architecture - Zen Resti Maulana; Eka Fitrianto; Muhammad Ilhamdi Rusydi; Asrul Azani Mahmood (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
Effective and efficient laboratory inventory management is crucial to support academic and research activities in higher education. The manual system currently used to manage eight laboratories in the electrical engineering department often leads to various problems, such as recording errors, asset loss, and inaccuracy in reporting. This is the urgency of establishing an integrated information system to improve the accuracy and efficiency of laboratory inventory management. This research aims to digitize the laboratory inventory through the implementation of an application-based laboratory inventory management information system, namely Silab Elektro. In addition, this system also aims to increase transparency and accountability in laboratory asset management. This information system was developed using UML (Unified Modeling Language) modeling with MVC (Model-View-Controller) architecture. This research produces a laboratory information system that can manage equipment inventory more effectively and efficiently, as well as improve data accuracy.